Reflecting on a journey of resilience in children's blood and cancer nursing. Issue 2 (4th March 2018) - Aburn, Gemma Elizabeth; Hoare, Karen; Gott, Merryn
Abstract: Reflective practice is recognised as an integral part of being a highly skilled and successful health care professional. Many benefits have been identified from being a reflective practitioner including the opportunity for critical thinking, growing self-awareness and supporting individual resilience. There is a growing body of literature recognising the negative emotional impact that caring for children with cancer and blood disorders can have on health professionals. Currently there is an emerging interest in a more strengths-based approach focused on maintaining staff wellbeing. Resilience has been suggested as a framework for coping and maintaining wellbeing in areas, like children's oncology and has been used as a term to describe the 'surviving' health professional. This paper explores the first author's (GA) experiences of being a children's oncology nurse and paediatric palliative care nurse specialist in the context of existing empirical and theoretical literature, with a particular focus on how GA developed resilience. Reflective examples of practice are used within the context of themes identified from a recent literature review exploring how resilience is defined within empirical literature.